(untitled) (Huellas, 2020)
The southwest region of Buenos Aires province is an area located in the south of the Pampas region (Argentina), that concentrates 12% of the national agricultural production. In spite of the existence of ample research on the climate of this region, neither thermal and rainfall cycles and tendencies, nor the cycles of dry and wet events, have been studied yet. For these reasons, this research aimed at evaluating the periodicity of thermal and rainfall events during the period 1970-2016. For such a purpose, daily meteorological series were analyzed through a Mann-Kendall test, the Standardized Precipitation Index and the Continuous Wavelet Transform. For temperature, results showed the existence of a positive and significant trend in most of the area, except in the north. Rainfall events took place all over the study area simultaneously, and they coincided with El Niño or La Niña events. Less intense precipitation events occurred in a heterogeneous way. The periodicity of thermal and rainfall events made evident a spatial inconsistency as the north was characterized by seasonal and annual cycles and in the south the cycles were heterogeneous. The results obtained provide decision-makers with a useful database to frame territorial planning with a view to achieving sustainable development.